Effectiveness of water hyacinth (eichhornia crassipes) in treatment of wastewater at Gebeng industrial area - Nurshahrina, Ahmad Zahir (2019)
Water pollution is a serious issues nowadays especially rivers, lake or pond near the industrial area. This is because of the wastewaters from industry are discharge into it after a few treatments. This scenario is dangerous and harmful to human, but also to environment especially for aquatic life including plants and animals. Phytoremediation is one of bio-green alternatives that can treat polluted water effectively. Mechanism of this process is using aquatic plants where these plants absorb the contaminant from the water and the water become clean without giving harmful to these plants. Water hyacinth (eichhornia crassipes) is one of the aquatic plants that undergo phytoremediation process effectively including in removing of heavy metal such as plumbum, cadmium and zinc. This study is to determine the effectiveness of water hyacinth (eichhornia crassipes) in treatment of wastewater near industrial. This study was conducted for 3 weeks. The concentrations of wastewater were 50%, 75% and 100%. From this research, the highest removal efficiency in percentage after 3 weeks for BOD (mg/l) was 35.78%, COD (mg/l) was 62.50%, pH was 38.57%, TSS (mg/l) was 50%, NH3-N (mg/l) was 84.91%, turbidity (NTU) was 42.34%, Plumbum (mg/l) is 70.27%, Cadmium (mg/l) was 77.27%, Zinc (mg/l) was 83.64%. While, for increasing removal in percentage after 3 weeks for dissolved oxygen (mg/l) was 41.52%. The removal efficiency of pollutants for treatment was more effective for wastewater at 50% concentration of wastewater compared 75% and 100%.